Waterborne Zoonotic Bacterial Pathogens: Review - Ozdan Akram Ghareeb; Qahtan Adnan Ali (Zien Journals, 2023)
Zoonoses infections are among the major public health issues confusing, as pandemics emergences intermittently causing significant global human and economic losses. The aim of this review is to summarize the most prominent waterborne bacterial pathogens of zoonotic origin, along with basic prevention methods. Excretions and waste products are most sources of waterborne zoonotic pathogens, as these substances are used as a means of transmission from the animal to the aquatic environment. Water is one of the ways of transmission of infection, especially through drinking water. Among these life-threatening bacterial pathogens is Bacillus anthracis , Campylobacter jejuni, which causes enteritis in humans and animals , Escherichia coli that causes hemorrhagic enteritis, Salmonella enterica that lead to enteritis, and Vibrio cholera which causes gastroenteritis and blood poisoning, may lead to death. For prevention, zoonotic pathogens must be controlled in animal reservoirs, along with proper disposal of animal waste as well as protecting surface water from animal waste and also sterilizing drinking water. In this review, we concluded the need to apply the qualitative approach to sterilization of drinking water according to international standards.
Keywords: Zoonoses infections; drinking water; bacterial pathogens